Poverty Level Forecasting in Maluku Province Using the Exponential Smoothing Method - A. Manuputty; R. Patiekon; M. Z. Waliulu; R. Siwalette; D. C. Latumahina; M. Y. Matdoan (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to predict the poverty rate in Maluku Province in 2021-2025 using the Exponential Smoothing method. The Exponential Smoothing method is a moving average forecasting method that gives exponential or multilevel weight to the latest data so that the latest data will get greater weight. The data in this study were sourced from the Central Bureau of Statistics for Maluku Province. In this study, the results obtained were a comparison of several Exponential Smoothing methods, namely Simple Exponential Smoothing, Brown Linear Trend, and Holt Linear Trend. The best method for forecasting poverty levels in Maluku Province was obtained, namely the Holt Linear Trend Exponential Smoothing method with MAPE (3.251), RMSE (1.057), and MAE (0.722) values. Therefore, the poverty rate in Maluku Province is estimated at 18.14 in 2021, 18.29 in 2022, 18.44 in 2023, 18.59 in 2024, and 18.74 in 2025 with intervals between 4.46 and 33.02.